Pharmacodynamic interaction of fenugreek with insulin and glimepiride in streptozotocin-induced oxidative stress in Sprague Dawley rats - Chiluka, Haritha; Alla, Gopala Reddy; Yerradoddi, Ramana Reddy; Banothu, Anil Kumar (Journal of Advanced Veterinary and Animal Research, 2015)
This study was aimed to assess the effect of fenugreek-insulin-glimepiride interaction on oxidative stress in streptozotocin-induced diabetic rats. A total of 56 male Sprague-Dawley rats were randomly divided into 7 groups (n=8); group 1: served as Sham, group 2: Diabetic control, groups 3, 4 and 5: served as individual treatment group, groups 6 and 7: treated with combination of insulin-fenugreek and glimepiride-fenugreek, respectively. Serum creatinine levels of the rats were estimated at 4th and 8th weeks during treatment. Thiobarbituric Acid Reactive Substances (TBARS), Glutathione (GSH) and protein carbonyls were estimated in the kidney homogenate, and relative kidney weights were measured at the end of the experiment. Present study indicated that the levels of TBARS and protein carbonyls significantly increased in group 2 and decreased in groups 3 to 7. On the other hand, groups 6 and 7 showed significantly lowered values compared to the individual treatment groups. The concentration of GSH was significantly decreased in group 2 and significantly increased in groups 3 to 7, and group 7 showed significantly higher concentration among all the treated groups. The serum creatinine concentration in group 2 was significantly higher and all treatment groups (3 to 7) showed significantly lowered values at 4th and 8th wks after treatment. The individual treatment groups (3, 4 & 5), antagonised the significant alteration in the antioxidant parameters, and their combination was revealed synergism by improving the oxidative status in diabetic rats. http://dx.doi.org/10.5455/javar.2015.b89